2022
DOI: 10.1111/jocn.16473
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of hospital‐acquired mucous membrane pressure injury: A five‐year analysis

Abstract: Background: Pressure injuries on mucous membranes are caused by pressure from medical devices at the site of injury and differ to those on the skin. Intensive care patients, who have multiple devices in situ, are particularly vulnerable. There is a significant knowledge gap regarding mucous membrane pressure injury (MMPI) incidence in acute hospital settings. Aim:To analyse MMPI incidence and characteristics in a tertiary acute general hospital. Methods:A secondary data analysis of hospital clinical incident r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results from these studies are in contrast to the calculated incidence of 30.4% found in one study (Coyer et al, 2015). More recently, an Australian study of mucosal pressure injury incidence reported a very low hospital‐wide hospital‐acquired incidence of .1% (Fulbrook, Lovegrove, & Butterworth, 2022). However, when intensive care versus non‐intensive care subgroups were compared, intensive care incidence was 80 times greater (2.4%) than that of non‐intensive care patients (.03%).…”
Section: Discussionmentioning
confidence: 99%
“…The results from these studies are in contrast to the calculated incidence of 30.4% found in one study (Coyer et al, 2015). More recently, an Australian study of mucosal pressure injury incidence reported a very low hospital‐wide hospital‐acquired incidence of .1% (Fulbrook, Lovegrove, & Butterworth, 2022). However, when intensive care versus non‐intensive care subgroups were compared, intensive care incidence was 80 times greater (2.4%) than that of non‐intensive care patients (.03%).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, MDR-MM PI is the local mucosal injury caused using medical devices, a distinct type of MDRPI. Because of the histological differences between mucosa and skin, we cannot use the PI staging system of the NPUAP based on skin anatomical structure to stage the PI of the mucosa [12,13].…”
Section: Introductionmentioning
confidence: 99%